Kota Seriemas Golf & Country Club / Alya Syamila Abdul Kadir - Abdul Kadir, Alya Syamila (Faculty of Business and Management, 2023)
This report is on practical training, which is covered in the course MGT 666, which is where it requires students to take to complete their degree. Practical training is an initial job training programme for students who will graduate from their studies and enter working life. I have already completed my practical training at Kota Seriemas Golf & Country Club starting on March 1, 2023, and finished on August 15, 2023. In this report, I have explained the background of this company, including its location, operating hours, vision, mission, and values. I was assigned a part of the marketing and sales group. Everything I contribute including my work is like what the staff does. I was granted the chance to learn how to organise my paperwork, connect and communicate with clients and other employees, handle administration work as part of my everyday duties, and many other skills. Next, further information about the business is also available. Information like the type of business done here, the goods or services provided to customers, the management style employed here, and other such things. Additionally, I had the opportunity to interact with many experienced and professional individuals including General Manager, Mr. Shahril, Mr. Ramiriz, the Operations Manager, Mrs. Zaihasra, the Manager of Human Resource department, AHR employees Ms. Poh Jin, Ms. Eliz, Mr. Fauzie, and many others. Not only that, but I was also able to identify swot analysis at KSGCC. I can determine this company's standing in the market based on that. At the conclusion of my report, I give some solutions to the issues the organisation faces. Finally, I gained a lot of knowledge and experience working in an actual work environment while completing my industrial training at KSGCC.